Fuelwood savings and carbon emission reductions by the use of improved cooking stoves in an Afromontane Forest, Ethiopia - Dresen, E.; Vries, B. de; Herold, Martin; Verchot, Louis V.; Müller, R. (MDPI, 2014)
In many Sub-Saharan African countries, fuelwood collection is among the most important drivers of deforestation and particularly forest degradation. In a detailed field study in the Kafa region of southern Ethiopia, we assessed the potential of efficient cooking stoves to mitigate the negative impacts of fuelwood harvesting on forests. Eleven thousand improved cooking stoves (ICS), specifically designed for baking Ethiopia’s staple food injera, referred to locally as “Mirt” stoves, have been distributed here. We found a high acceptance rate of the stove. One hundred forty interviews, including users and non-users of the ICS, revealed fuelwood savings of nearly 40% in injera preparation compared to the traditional three-stone fire, leading to a total annual savings of 1.28 tons of fuelwood per household. Considering the approximated share of fuelwood from unsustainable sources, these savings translate to 11,800 tons of CO2 saved for 11,156 disseminated ICS, corresponding to the amount of carbon stored in over 30 ha of local forest. We further found that stove efficiency increased with longer injera baking sessions, which shows a way of optimizing fuelwood savings by adapted usage of ICS. Our study confirms that efficient cooking stoves, if well adapted to the local cooking habits, can make a significant contribution to the conservation of forests and the avoidance of carbon emission from forest clearing and degradation.